2006
DOI: 10.1099/jmm.0.46661-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of swarming and virulence factor expression in Proteus mirabilis by resveratrol

Abstract: Resveratrol (3,5,4-trihydroxy-trans-stilbene) is a phytoalexin compound with anti-inflammatory and antioxidant activities. The effect of resveratrol on swarming and virulence factor expression of Proteus mirabilis, an important pathogen infecting the urinary tract, was determined on swarming agar plates with and without the compound. Bacteria harvested at different times were assayed for cell length and the production of flagella, haemolysin and urease. Resveratrol inhibited P. mirabilis swarming and virulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 50 publications
6
79
2
2
Order By: Relevance
“…These results were similar to those reported by Ahuja et al [13] and Labrecque et al [28] who observed that cranberry juice concentrate had neither antibacterial activity on uropathogenic E. coli nor on Porphyromonas gingivalis. The results were also similar to those obtained by Wang et al [31] who suggested that the inhibitory effect of resveratrol, a naturally occurring phytoalexin, on P. mirabilis swarming and virulence factors expression is unlikely to be due to its inhibitory effect on bacterial growth.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results were similar to those reported by Ahuja et al [13] and Labrecque et al [28] who observed that cranberry juice concentrate had neither antibacterial activity on uropathogenic E. coli nor on Porphyromonas gingivalis. The results were also similar to those obtained by Wang et al [31] who suggested that the inhibitory effect of resveratrol, a naturally occurring phytoalexin, on P. mirabilis swarming and virulence factors expression is unlikely to be due to its inhibitory effect on bacterial growth.…”
Section: Discussionsupporting
confidence: 80%
“…Wang et al [31] evaluated the effect of resveratrol on swarming of P. mirabilis and they observed that this compound also inhibited P. mirabilis swarming in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Although salmeterol also seems to protect the respiratory epithelium against H. influenzae-induced damage [126], in vivo data show that inhalation of this bronchodilator may negatively influence the effective clearance of NTHi from the murine respiratory tract [127]. In contrast, resveratrol has been shown to ameliorate Serratia marcescens-induced acute pneumonia in rats [128], inhibit swarming and virulence factor expression in Proteus mirabilis [129], be a potential candidate against various Helicobacter pylori-related gastric pathogenic processes [130], and selectively inhibit N. gonorrhoeae and N. meningitidis [131]. in urinary tract infections caused by uropathogenic Escherichia coli [132].…”
Section: Impact Of Anti-inflammatory Therapies On Bacterial Respiratomentioning
confidence: 99%
“…When the swarm encounters a prey, they kill and lyse the cells using lytic enzymes by a technique called as 'rippling' which helps the bacteria to effectively lyse and absorb the nutrients of the prey (Velicer et al, 2000;Berleman et al, 2008). A similar type of social behaviour is also seen in enteric bacterium Proteus mirabilis, which uses the swarming technique for movement of the colony and for collective preying (Wang et al, 2006b). There are several other behaviours in bacteria that have evolved over time as a means to survive and sense the environment in a solitary as well as collective manner.…”
Section: Social Behaviours In Bacteriamentioning
confidence: 99%